Localisation and metabolism of reactive oxygen species during Bremia lactucae pathogenesis in Lactuca sativa and wild Lactuca spp - Sedlárová, Michaela; Luhová, Lenka; Petrivalský, Marek; Lebeda, Ales (Plant physiology and biochemistry, 2007)
A plant's physiology is modified simultaneously with Oomycete pathogen penetration, starting with release and accumulation of reactive oxygen species (ROS). Localisation of superoxide, hydrogen peroxide, peroxidase and variation in their activity, and the isoenzyme profile of antioxidant enzymes peroxidase (1.11.1.7), catalase (EC 1.11.1.6), superoxide dismutase (EC 1.15.1.1) were studied in six genotypes of four Lactuca spp. (L. sativa, L. serriola, L. saligna and L. virosa) challenged with Bremia lactucae (race NL16). These factors were related to the differential expression of resistance during the course of 96h after inoculation (hai). Accumulation of hydrogen peroxide in infected cells together with enhanced activity of H(2)O(2)-scavenging enzymes in leaf extracts characterised resistant Lactuca spp. genotypes 6-12hai, and peaked at 48-96hai with expression of a hypersensitive reaction. Substantial changes of guaiacol peroxidase activity were detected only in the cytosolic enzyme; activities of the membrane-bound and the ion-bound enzymes were insignificant in the interactions of host genotypes and pathogen isolate examined. The most significant modifications of ROS metabolism were found in resistant L. virosa (NVRS 10.001 602), a genotype responding to pathogen ingress by a rapid and extensive hypersensitive reaction. Formation of the superoxide anion was not detected in either susceptible or resistant plants, and there was also no increase of superoxide dismutase activity or changes in its isozyme profile. The significance of precise balancing the intracellular level of hydrogen peroxide for variability of phenotypic expression of responses to B. lactucae infection in Lactuca spp. is discussed.
Keywords: Peroxidases; peroxid vodíku; reaktivní formy kyslíku; druhová specificita; Reactive Oxygen Species; genotyp; Hydrogen Peroxide; listy rostlin; superoxiddismutasa; Phenotype; Peronospora; peroxidasy; Species Specificity; antioxidancia; Lactuca; Plant Leaves; Antioxidants; salát (hlávkový); protein - isoformy; Plants; Superoxide Dismutase; fenotyp; Genotype; rostliny; Protein Isoforms